Detection, Prevalence and Phylogenetic Analysis of Feline Coronavirus in Malaysia - Sharif, Saeed (2010)
Feline coronavirus (FCoV) consisted of feline enteric coronavirus (FECV) and feline infectious peritonitis virus (FIPV) which cause a mild disease and fatal disease known as feline infectious peritonitis (FIP), respectively. There is neither effective vaccine, nor curative treatment for FIP, and a fast and reliable diagnosis would greatly assist in the management and control of the virus. In this study, a rapid and sensitive approach was established for detection of FCoV using reverse transcriptase polymerase chain reaction (RT-PCR) assay. In the attempt to improve the sensitivity and specificity of the assay, the RT-PCR assay was developed using SYBR Green 1 real-time RT-PCR. By using the RT-PCR assay the prevalence of FCoV was examined in 44 healthy and 28 sick cats suspected of FIP. Results showed FCoV infections in healthy and sick cats were of 84% and 89%, respectively. Phylogenetic analysis was performed on FCoV isolates obtained from 4 healthy and 10 sick cats. The sequence alignment revealed that the local isolates had 96% homology and fall into one main genetic cluster. These findings provided the first genetic information of FCoV in Malaysia. In another study, a duplex RT-PCR assay was developed for detection of mRNS of FCoV in blood samples from 40 healthy and 10 FIP-suspected cats. The results showed that 67.5% of healthy cats were FCoV-positive and the viral mRNA was detected in 15% of animals. In testing of FIP-suspected cats, all cases were positive FCoV with detectable mRNA. Since it is assumed that the viral replication in blood is associated with FIP, the duplex RT-PCR assay is more specific for detection of FIP. However, detecting the viral mRNA by the duplex RT-PCR in asymptomatic cats should be interpreted in conjunction with other clinical findings.